Recurrent parotitis in children - Bhattarai M; Wakode P (Journal of Indian Association of Pediatric Surgeons, 2006)
Recurrent parotitis is an uncommon condition in children. Its etiological factors have not been proved till date although causes due to genetic inheritance, local autoimmune manifestation, allergy, viral infection and immunodeficiency have been suggested. The exact management of this disorder is not yet standardized, but a conservative approach is preferred and all affected children should be screened for Sjogren′s syndrome and immune deficiency including human immunodeficiency virus. We report a 12 years female child who presented with 12 episodes of non-painful recurrent swellings of the bilateral parotid gland in the past 3 years.